"Cataplexy" and muscle ultrasound abnormalities in Coffin-Lowry syndrome. Issue 2 (February 1998) - Crow, Y J; Zuberi, S M; McWilliam, R; Tolmie, J L; Hollman, A; Pohl, K; Stephenson, J B
Abstract : The Coffin-Lowry syndrome is a rare cause of mental retardation recognised by its distinctive facial and digital features. We have observed an unusual, non-epileptic, cataplexy-like phenomenon in three subjects with the syndrome and we speculate that this feature may go unrecognised. We also provide evidence of neuromuscular dysfunction as part of the phenotype by showing abnormalities on muscle ultrasound in four gene carriers.